Bill Morrison, l’invité des morts - Gilles Berger; Xavier Fayet; Jérôme Ters (Mise au Point)
We are attempting here, by examining Bill Morrison’s 2007 short film Who by water, to identify and to determine the nature of the viewer’s experience and, on that basis, to propose a definition of cinema as a phenomenon rather than a language. From a certain ontological point of view, cinematic image becomes a way of interrogating the viewer’s role and position, but also of rethinking the status of the filmmaker in order to better understand – beyond outdated categories such as documentary or fiction – the constantly renewed dialogue between sequential cinematic images and their perception.